Mycetoma in West Africa. (16th March 2021) - Oladele, Rita Okeoghene; Ly, Fatimata; Sow, Douduo; Akinkugbe, Ayesha O; Ocansey, Bright K; Fahal, Ahmed H; van de Sande, Wendy W J
Abstract: Background: Mycetoma is a neglected disease, which is socioeconomically important, and with the possibility of permanent disability in infected persons if not treated early. This is especially true in resource-limited settings such as West Africa, where there is a lack of facilities and skilled personnel to make a definitive laboratory diagnosis. Countries in West Africa have similar climatic conditions to Sudan. The majority of patients seek medical care very late, when there is already bone involvement, resulting in amputations. This results in poor capture of the true burden of the problem in the literature. Methods: A review of the literature revealed about 2685 documented cases in West Africa from 1929 to 2020; from 15 out of 16 countries, Senegal accounted for 74.1% (1943) of cases in the subregion. Results: The majority of lesions were found on the foot; however, other body parts were also reported. Rural dwellers accounted for most cases. Only 547 (20.4%) cases had identified isolates reported. Actinomycetoma accounted for 47.9% of cases, eumycetoma 39.7% and unidentified pathogens 12.4%. Actinomadura pelletieri was the predominant pathogen isolated (21.4%; 117 isolates). Conclusion: There is a dire need for capacity building, provision of facility and health education to raise awareness of this debilitating disease in West Africa.